Implementasi Web 3D untuk Pembelajaran Basic Life Support CPR dengan Teknik Gamifikasi - Verdian, Ihsan (Journal of Digital Ecosystem for Natural Sustainability, 2024)
The focus of this research is on designing an alternative interactive 3D learning media specifically for basic life support CPR for students. The goal is to provide an interactive learning media option on basic life support CPR at School. The basic life support CPR material is combined with 3D interactive media using Gamification and Game Development Life Cycle (GDLC) methods. This learning media integrates basic life support CPR content, game scenarios, and interactive elements to create an engaging and realistic learning experience. The expected outcome of this research is an engaging learning media for students to learn basic life support CPR and to facilitate educators in delivering this material effectively. Application testing will be conducted through game testing, public beta, and questionnaires.